Floor water inrush analysis based on mechanical failure characters and microseismic monitoring. (February 2021) - Ma, K.; Sun, X.Y.; Tang, C.A.; Yuan, F.Z.; Wang, S.J.; Chen, T.
Highlights: The coal floor stress affected by the infinite-range water pressure is obtained. During the initial weighting, the failure depth of the coal seam is within 13 m. The hazard of floor water inrush is controlled by the depth of the shear failure. A comprehensive method to evaluate the state of the coal seam floor is proposed. The proposed method can also be used to analyze water inrush problems in tunnels. Abstract: Failure characteristics of the coal seam floor above-confined aquifer are the key to understanding water inrush mechanism during mining. Due to the heterogeneity of coal strata and complex structures of the coal seam floor, it is still difficult to comprehensively reveal failure characteristics of the coal seam floor and accurately determine the floor failure depth during mining above the confined aquifer. In this research, Dongjiahe coal mine, where the coal seam floor is exposed to abundant Ordovician limestone water, is taken as a case study. An improved theoretical model is firstly proposed, in which the whole confined aquifer in the floor is taken into account for stress and failure analysis. Then, RFPA (Rock Failure Process Analysis), a numerical test method considering the heterogeneity of coal and rock, is adopted to simulate the progressive failure process of coal seam floor during mining. Moreover, The microseismic monitoring system is constructed and the 3D visualization is realized through virtual reality, which can sense the initiation and expansion of microdamage in real-time. Based on microseismic monitoring results, we investigate and calculate the floor disturbance depth. By comparing the failure characteristics obtained by different methods, we discuss the pros and cons of the above methods. Finally, a comprehensive analysis method and roadmap are proposed to analyze the failure characteristics of the coal seam floor more accurately based on theoretical calculation, numerical simulation, and microseismic monitoring. The results can provide some reference for the evaluation and prevention of floor water inrush hazards.